The impact of strain, constraints, and morality on different cyberbullying roles: A partial test of Agnew’s general strain theory - Li, Wanqi; Peng, Huaxin (Frontiers in Psychology, 2022)
The strain has been well studied in traditional bullying, and recent research has begun to explore it in cyberbullying behavior. Drawing from General Strain Theory, the current study empirically examined the relationship between strain and the cyberbullying behavior of perpetrators and bully-victims, respectively. Meanwhile, this study also considered the influences of the protective variables (e.g., constraints and morality) on the strain, which may potentially reduce the risks of participating in cyberbullying. The sample comprised 928 Chinese internet users (Male=490, Female=438) aged between 16 to 50. We identified the prevalence of cyberbullying in China, in which the percentages of cyberbullying perpetrators, cyberbullying victims, and cyber bully–victims were 23.40%, 23.20%, and 37.40%, respectively. This study mentioned a noteworthy phenomenon: cyberbullying victims quickly became cyberbullying perpetrators when they were cyberbullied. Secondly, according to the binary logistic regression, we hold that the strain was significantly related to cyberbullying behaviors, as individuals with low levels of self-control showed a higher tendency to participate in cyberbullying. As for protective factors, the results showed that constraints and morality can reduce the negative consequences of strain and then against cyberbullying, exploring the possibilities of using constraints and morality as variables to decrease strain and prevent cyberbullying. Thus, the unique values of this study are using the GST theory to investigate the empirical link between strain and cyberbullying between different roles in a new cultural and social background, demonstrating that negative emotion and low self-control had influences on strain and cyberbullying behaviors. Meanwhile, this study also contributes by discussing the implications for future research and practicing efforts targeting how to decrease the risks of cyberbullying engagement, for example, we suggest that the prevention and intervention of cyberbullying should adopt a cross-sectoral response to help individuals to view cyberbullying, vent dissatisfaction and relieve strain in the right way.